Tropical secrets : Holocaust refugees in Cuba - Engle, Margarita (New York : Holt, 2009)
Escaping from Nazi Germany to Cuba in 1939, a young Jewish refugee dreams of finding his parents again, befriends a local girl with painful secrets of her own, and discovers that the Nazi darkness is never far away.
Booklist
Bulletin (Center for Children's books)
Young Adult.
Young Adult
Keywords: Holocaust, Jewish (1939-1945) -- Juvenile fiction; Jews -- Cuba -- History -- 20th century -- Juvenile fiction; Novels in verse; Refugees -- Juvenile fiction; Historical fiction; Holocaust, Jewish (1939-1945) -- Fiction; Jews -- History -- Fiction; Novels in verse; Refugees -- Fiction; Historical fiction; Holocaust, 1933-1945 -- Fiction; Jews -- Cuba -- History -- Fiction; Refugees -- Fiction; Cuba -- History -- 1933-1959 -- Juvenile fiction; Cuba -- History -- Fiction; Cuba -- History -- Fiction